Morse taper internal connection implants: would abutment reseating influence retention? - Stenio Cardoso Rabelo; Sheyla Viana Omonte; Sarita Pires Vieira; Wellington Correa Jansen; Paulo Isaias Seraidarian (Universidade Estadual de Campinas, 2015)
Aim: To investigate whether the removal and reseating of the abutment influences the retention of Morse taper implant system. Methods: Two Morse taper implant systems were selected: Bicon Dental ImplantTM system (Bicon, LLC, Boston, MA, USA) and Kopp Implant® system (Kopp®, Curitiba, PR, Brazil). In both systems, the abutment is connected to the implant with a locking taper. To seat the abutment, the same vertical force was applied in both systems. It was measured the compressive force necessary to engage effectively the locking taper connection and the tensile force to displace it. Results: The compressive force was determined by four activations in each abutment-implant set, and the sum of these forces was 21 N and 17 N in the BiconTM and Kopp® systems, respectively. Next, a tensile test was performed, revealing that the BiconTM system presented a 208 N resistance, whereas it was 194 N in the Kopp® system. Other three rounds of compression and tensile loads were applied, removing and reseating the abutment. We obtained the following tensile values: 367 N, 500 N and 756 N in the BiconTM System and 336 N, 360 N and 420 N in the Kopp® system. Conclusions: When the sets were subjected to repeated rounds of compressive and tensile forces, displacing and reseating the abutment, the tensile value increased.